Spontaneous Magnetization of Quantum XY-chain from Finite Chain Form-factors - Iorgov, N.Z. (Відділення фізики і астрономії НАН України, 2010)
Using the explicit factorized formulas for matrix elements (formfactors) of the spin operators between the eigenvectors of the Hamiltonian of a finite quantum XY-chain in a transverse field, the spontaneous magnetization for σ^x and σ^y is re-derived in a simple way. Використовуючи факторизованi формули для матричних елементiв (формфакторiв) спiнових операторiв мiж власними векторами гамiльтонiана скiнченного квантового XY-ланцюжка в поперечному полi, дано простий вивiд формули для спонтанної намагнiченостi σ^x та σ^y.